Improvement of Immunogenicity of Meningococcal Lipooligosaccharide by Coformulation with Lipidated Transferrin-Binding Protein B in Liposomes: Implications for Vaccine Development - Mistretta, Noëlle (American Society for Microbiology, 2012)
Among various meningococcal antigens, lipooligosaccharide (LOS) and recombinant lipidated transferrin-binding protein B (rlip-TbpB) are considered to be putative vaccine candidates against group B Neisseria meningitidis. In the present work, we report the development of a new liposome-based vaccine formulation containing both rlip-TbpB and L8 LOS. The endotoxic activity of the liposomal LOS was evaluated in vitro using the Limulus Amebocyte Lysate assay and compared to the endotoxic activity of free LOS. Above a 250:1 lipid/LOS molar ratio, liposomes were shown to effectively detoxify the LOS as the endotoxic activity of the LOS was reduced by more than 99%. Immunogenicity studies in rabbits showed that the presence of rlip-TbpB dramatically increased the immunogenicity of the LOS. While the formulation raised a strong anti-TbpB response, it elicited a higher anti-LOS IgG level than the liposomal LOS alone. Sera from rabbits immunized with rlip-TbpB/liposomal LOS displayed increased ability to recognize LOS on live bacteria expressing the L8 immunotype and increased anti-LOS-specific bactericidal activity compared to sera from rabbits immunized with liposomal LOS alone. Measurement of interleukin-8 (IL-8) produced by HEK293 cells transfected with Toll-like receptor (TLR) after stimulation with rlip-TbpB showed that the protein is a TLR2 agonist, which is in accordance with the structure of its lipid. Furthermore, an in vivo study demonstrated that the lipid moiety is not only required for its adjuvant effect but also has to be linked to the protein. Overall, the rlip-TbpB/LOS liposomal formulation was demonstrated to induce an effective anti-LOS response due to the adjuvant effect of rlip-TbpB on LOS.